The Effect of Village Funds And Capital Expenditure on Welfare Through Poverty Mediation in District/City in East Java Province - Nurharibnu Wibisono; Indah Yuliana; Nanik Wahyuni (Politeknik Negeri Madiun, 2023)
The purpose of this study was to analyze the effect of Village Funds and Expenditure Capital on welfare through poverty in 30 regencies/cities (29 regencies and 1 Batu city) in East Java province in 2015–2022. Secondary data on Village Funds and Capital Expenditures were obtained from the website of the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. Secondary data on poverty (number of poor people) and welfare (IPM) were obtained from the website of the Central Statistics Agency (BPS) of East Java Province. The data analysis technique used path analysis with the SmartPLS 3 tool. The results showed that partially the Village Fund had a significant positive effect on poverty and the Village Fund had a significant positive effect on welfare. Capital Expenditure has a significant positive effect on poverty and Capital Expenditure has a significant positive effect on welfare. Poverty has a significant negative effect on welfare. Village Funds have a significant indirect negative effect on welfare through poverty. Capital Expenditures have a significant indirect negative effect on welfare through poverty.